Integrating Pricing and Inventory Control: Is it Worth the Effort? - Lisa Gimpl-Heersink; Christian Rudloff; Moritz Fleischmann; Alfred Taudes (BuR - Business Research, 2008)
In this paper we first show that the gains achievable by integrating pricing and inventory control are usually small for classical demand functions. We then introduce reference price models and demonstrate that for this class of demand functions the benefits of integration with inventory control are substantially increased due to the price dynamics. We also provide some analytical results for this more complex model. We thus conclude that integrated pricing/inventory models could repeat the success of revenue management in practice if reference price effects are included in the demand model and the properties of this new model are better understood.
urn:nbn:de:0009-20-13953
Keywords: 650; inventory management; pricing; reference price; stochastic demand model; Lagermanagement; Preismanagement; Lagerhaltungsmodell; Operations Research